Event processing : designing IT systems for agile companies - Chandy, K. Mani; Schulte, W. Roy (New York, United States : McGraw Hill, 2010)
This book explains, step-by-step, how to design, deploy, and use event-processing (EP) systems to detect and respond to business anomalies, threats, and opportunities.
Includes bibliographical references (p. 215-218) and index.
IT
Keywords: Service-oriented architecture (Computer science); Event processing (Computer science); Discrete-time systems; Business -- Data processing; Business enterprises -- Computer networks